2021
DOI: 10.1002/ece3.7553
|View full text |Cite
|
Sign up to set email alerts
|

Six minutes to promote change: People, not facts, alter students' perceptions on climate change

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Partisan evaluations of FFs do not simply reflect an evaluative charitability extended to members of the perceivers in-group (e.g., Valdesolo & DeSteno, 2007), nor do they simply reflect the excusing of actions that could benefit the in-group. Given that elite political figures can have more potential to shape their own side's positions and beliefs than do nonpolitical subject matter experts (e.g., Sauer et al, 2021), then the partisan reluctance to condemn policy FFs may contribute to misinformation and division among the electorate.…”
Section: Political Falsehoodsmentioning
confidence: 99%
“…Partisan evaluations of FFs do not simply reflect an evaluative charitability extended to members of the perceivers in-group (e.g., Valdesolo & DeSteno, 2007), nor do they simply reflect the excusing of actions that could benefit the in-group. Given that elite political figures can have more potential to shape their own side's positions and beliefs than do nonpolitical subject matter experts (e.g., Sauer et al, 2021), then the partisan reluctance to condemn policy FFs may contribute to misinformation and division among the electorate.…”
Section: Political Falsehoodsmentioning
confidence: 99%
“…Van der Linden et al's (2015) findings have been challenged, in particular the authors' data analysis and conclusions (Kahan, 2017), criticisms which the original authors have responded to (van der Linden et al, 2017). Some researchers have argued that communicating consensus entrenches rather than updates already-held beliefs, or creates a 'backfire' effect (Sauer et al, 2021;van der Linden et al, 2017).…”
Section: Empirical Evidence For the Gateway Belief Modelmentioning
confidence: 99%
“…This sample thus represents a relatively small portion of the population; however, it is deemed adequate for analysis because our questionnaires are more comprehensive than those typically used in other studies. We utilized methods developed by Walker et al (2017) and later refined by Sauer et al (2021) for our study on responder determinants. We chose three environmental-related products emphasizing environmental literacy (i.e., knowledge, attitude, and behavior).…”
Section: Field Investigationmentioning
confidence: 99%
“…In addition, many believe that their opinions, attitudes, and beliefs are sufficiently malleable to change if they are presented with new information (Mao et al, 2018). Consequently, providing additional knowledge effectively addresses misconceptions and poor attitudes and promotes acceptable behavior (Sauer et al, 2021). Previous research has demonstrated that those who understand the underlying causes of environmental illiteracy are more likely to believe that human actions contribute to the decline of riparian areas (Lee et al, 2015; Zheng, Arif, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation